(Un)Exceptional: Representations of the Marginalisation of Black Female Queer Desire in Chinelo Okparanta's “Under the Udala Trees” and Leona Beasley's “Something Better Than Home” - Mosiakgabo, Gogontle Rorisang (Department of English Language and Literature, 2023)
This thesis aims to assess the representations of Black same-sex desiring women, specifically in the contexts of the United States of America and Nigeria. The primary aim of this study is to explore and critique the notion of U.S. sexual exceptionalism and homonormativity as theorised by Jasbir Puar's Terrorist Assemblages. In doing so, I aim to show that while the United States of America positions itself as more progressive than countries that continue to criminalise and persecute same-sex desiring people, queer people in both contexts continue to be marginalised and face similar challenges that are a result or cause of this marginalisation. This comparative thesis of Chinelo Okparanta's Under the Udala Trees and Leona Beasley's Something Better Than Home examines the ways in which religion; notions of secrecy and censorship; as well as compulsory heterosexuality and homophobic violence contribute to the marginalisation of Black queer women in both the United States of America and Nigeria.